IMPLEMENTASI KEBIJAKAN SERTIPIKAT TANAH ELEKTRONIK PADA KANTOR PERTANAHAN KOTA TOMOHON - Ria Raphita Br Pasaribu; Joyce J. Rares; Shirley Y. V. I. Goni (GoAcademica Research dan Publishing, 2025)
The study aims to analyze the implementation of the policy. Data analysis uses the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that the implementation of the electronic land certificate policy in Tomohon City has not yet run optimally. In terms of communication, although socialization has been carried out through various channels, many community members still do not understand the procedures and benefits of electronic certificates and remain hesitant due to concerns about data security and the absence of physical documents. In terms of resources, policy implementation is hindered by limited human resources, insufficient technical competence, and inadequate technological infrastructure such as computers, internet networks, and other supporting devices. In terms of disposition, implementers demonstrate positive attitudes and strong commitment in supporting the implementation and finding solutions to emerging technical obstacles. The study concludes that the implementation of the electronic land certificate policy at the Tomohon City Land Office still needs to be improved, particularly in public communication, resource readiness, and infrastructure strengthening, so that digital land administration services can operate more effectively, efficiently, and be well accepted by the community.